THE ROLE OF THE NATIONAL LAND AGENCY OF GIANYAR REGENCY IN OPTIMIZING THE OWNERSHIP OF ELECTRONIC LAND CERTIFICATES AS AN EFFORT TO PREVENT DOUBLE CERTIFICATES - Sang Ayu Made Ary Kusumawardhani; Made Nani Supartini (International Conference on Multidisciplinary Research Perspective, 2025)
The overlap of land certificates involves various legal aspects, including Law Number 5 of 1960 concerning the Basic Agrarian Principles (UUPA), Government Regulation Number 24 of 1997 concerning Land Registration, as well as the procedures applied in the Prona program. The purpose of this research is to analyze the role of the National Land Agency of Gianyar Regency in optimizing the ownership of electronic land certificates as a strategic measure to prevent double certificates.The type of research used in this study is empirical legal research. The research location is the National Land Agency Office of Gianyar Regency. The results of this study show that the implementation of electronic land certificates requires a longer transition period because the public has not yet fully trusted the existence of these electronic certificates, which also poses a challenge. The conclusion of this study is that the role of the National Land Agency of Gianyar Regency in optimizing the ownership of electronic certificates is very crucial in efforts to prevent double certificates. Through digital transformation, the Gianyar Land Agency encourages the integration of land data into a verified and transparent electronic system. The challenges faced by the National Land Agency of Gianyar Regency in optimizing electronic certificate ownership include uneven technological infrastructure, limited human resources who understand digital systems, and the low level of public literacy regarding the use of electronic documents. In addition, there are still technical obstacles such as overlapping old land data and challenges related to administrative culture.